What makes an effective antismoking campaign - insights from the trenches - Sarah Jane Beasley; Adam Barker; Michael Murphy; Toby Roderick; Tom Carroll (Sax Institute, 2020)
Objectives: This paper describes traditionally effective approaches for anti-smoking mass media advertising and explores challenges and future directions for campaign planning. The changing characteristics of the current smoking population and media landscape are examined. Type of program or service: Anti-smoking mass media advertising campaigns. Methods: We present a commentary on the established creative and media strategies proven to be effective in prompting quit attempts among smokers, discuss new challenges facing anti-smoking campaign managers today and propose considerations for the future. Results: Although evidence of effective approaches for tobacco control messaging and execution remains clear, the media landscape in Australia has changed dramatically in recent years with some audiences moving away from frequent and heavy television consumption towards online platforms and digital media channels. In addition, as smoking rates continue to fall, characteristics of current smokers are becoming increasingly relevant considerations for anti-smoking messaging and placement within a media environment that is becoming more expensive and fragmented. Funding anti-smoking advertising at the levels required to effectively prompt and maintain smoking cessation remains a high priority considering the extensive social and economic costs of smoking. Lessons learnt: Although it is known that hard-hitting, emotional and/or testimonial anti-smoking advertisements can be effective in prompting quit attempts, optimal media channel selection and media mix for reaching and engaging audience segments is dynamic in an ever-changing media landscape. Targeting media channels popular with lower socio-economic status (SES) smokers can efficiently achieve wide population exposure as well as effectively reaching population groups with higher smoking prevalence. A collaborative approach between health professionals, researchers, creative directors and media buyers is required to ensure advertising materials are communicating the right message for the audience, and that it is being delivered effectively.